PENGARUH PENGETAHUAN MASYARAKAT TERHADAP TINDAKAN PENCEGAHAN TUBERCOLOSIS : SEBUAH STUDI LITERATUR - Nashiir, Muhammad Rosyidin; Vinami Yulian (Bajang Institute, 2024)
Background: The increasing number of TB cases in Indonesia is often an unresolved problem. Therefore, the importance of knowledge about TB is one of the factors that support the prevention of the disease. Objective: To Knowing the effect of knowledge on Tuberculosis prevention. Method: The method used is a literature review with Google Scholar and PubMed data searches by identifying, screening, eligibility, and exclusion. Results: Research shows that there is an effect of education level on the prevention of tuberculosis. Suggestion: Literature review can be used as a reference on the influence of knowledge on the prevention of tuberculosis.